Analisis Penerapan Perhitungan Dan Pemotongan PPh 21 Atas Dosen Tetap Pada Politeknik Pos Indonesia - Satria, Muhammad Rizal; Fatmawati, Ade Pipit (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The tax sector is an essential source of income for the State, in addition to that the tax serves to financegovernment expenditures and regulate or implement government policies. One fee that is a source of stateincome is an income tax on individuals or often referred to as Article 21 income tax. In calculating PPh21, sometimes there are still people who make fundamental mistakes, such as incorrectly applyingapplicable tariffs. And this happened at Polytechnic Pos Indonesia, taxpayers who should be subject to aprogressive tax rate of 15% turned out to only be charged a scale of 5%, this caused at the end of the taxcalculation the permanent lecturers of Polytechnic Pos Indonesia experienced significant underpayments.The incorrect setting of these rates causes inconvenience for permanent lecturers because they have to payback taxes with a significant enough value. From the results of the analysis conducted, the calculation ofincome tax, the application of the amount of Gross income, Position Costs, PTKP, PKP, and 21 tax ratesfor permanent lecturers at Polytechnic Pos Indonesia is correct based on the applicable tax laws. Aftercomparing the results of calculations made by institutions, it was found that the tax rates applied to the PosIndonesia Polytechnic were following the Income Tax Law Number 36 of 2008 and the Tax DirectorGeneral Regulation Number Per-31 / PJ / 2012. The Pos Indonesia Polytechnic has also reported PPh 21by using SPT and SSP following the rules and regulations that apply correctly and adequately.